The path to circularity: A literature review of its application in Latin America - Andrade Carrasco, María Emilia (2023)
Present and future generations have a great concern about environmental issues such as the increase of contamination of natural resources and the loss of plant and animal life on earth due to excessive waste and its poor management, poor production practices and consumption habits. As a result of this concern, the main purpose of this research was to present the strategies and the framework that constitute the circular economy (CE) and to consider its application in Latin America. The methodology included a literature review using Scopus and Dialnet databases, applying the key terms “Circular Economy” and “Latin America”, the selection criteria were based on language, number of citations and publication date, which resulted in a statistical sample of 62 articles and reports. After completing the literature review of CE principal concepts, implementation strategies throughout different economic levels, opportunities and disadvantages for use, the researcher was able to see the potential for a global change in the economic system. Because there are clear differences in the application of a circular economy in different regions, the researcher found that an investigation into the socio-economic conditions of any particular region would be necessary before implementing a circular business model. The researcher found that in Latin America a circular economy with a focus on regenerative agriculture and a waste management sector with a waste-to-energy focus provided a high potential for success.